On the Physical Meaning of Parameters E0 and β in Dubinin's Theory - Fritz Stoeckli; Daniel Morel (CHIMIA)
A comparative study of limiting adsorption energies in microporous carbons and on graphitized carbon blacks shows that their difference is proportional to the quantity βE0 which appears in Dubinin’s theory. It follows that the characteristic energy E0 must be related to an average pore size, as found empirically. The affinity coefficient β, on the other hand, can be regarded as a shifting factor, directly related to the ratio of gas-solid adsorption potentials.